The montane trees of the Cameroon Highlands, West-Central Africa, with Deinbollia onanae sp. nov. (Sapindaceae), a new primate-dispersed, Endangered species - Cheek, Martin; Onana, Jean Michel; Chapman, Hazel M. (PeerJ, 2021)
We test the hypothesis that the tree species previously known as Deinbollia sp. 2. is a new species for science. We formally characterise and name this species as Deinbollia onanae (Sapindaceae-Litchi clade) and we discuss it in the context of the assemblage of montane tree species in the Cameroon Highlands of West-Central Africa. The new species is a shade-bearing, non-pioneer understorey forest tree species reaching 15 m high and a trunk diameter that can attain over 40 cm at 1.3 m above the ground. Seed dispersal has been recorded by chimpanzees (Pan troglodytes ellioti) and by putty-nose monkeys (Cercopithecus nictitans) and the species is used by chimpanzees for nesting. Cameroon has the highest species-diversity and species endemism known in this African-Western Indian Ocean genus of 42, mainly lowland species. Deinbollia onanae is an infrequent tree species known from six locations in surviving islands of montane (sometimes also upper submontane) forest along the line of the Cameroon Highlands, including one at Ngel Nyaki in Mambilla, Nigeria. Deinbollia onanae is here assessed as Endangered according to the IUCN 2012 standard, threatened by severe fragmentation of its mountain forest habitat due to extensive and ongoing clearance for agriculture. The majority of the 28 tree species of montane forest (above 2000 m alt.) in the Cameroon Highlands are also widespread in East African mountains (i.e. are Afromontane wide). Deinbollia onanae is one of only seven species known to be endemic (globally restricted to) these highlands. It is postulated that this new species is morphologically closest to Deinbollia oreophila, a frequent species at a lower (submontane) altitudinal band of the same range. Detailed ecological data on Deinbollia onanae from the Nigerian location, Ngel Nyaki, where it has been known under the name Deinbollia “pinnata”, is reviewed.
Keywords: Monoecious; High altitude; Forest clearance; Litchi group; Seed dispersal; Chimpanzee dispersal; Putty-nose monkey dispersal; Medicinal plant; Severe habitat fragmentation; Nigeria